The Karush-Kuhn-Tucker Optimality Condition for \(q\)-Rung Orthopair Fuzzy Optimization Problem - James, Josna; Jose, Shiny (Communications in Mathematics and Applications, 2023)
In this paper, we defined the interval form of \(α, β\) level set for triangular q-rung orthopair fuzzy (qROPF) number. To obtain a differentiability notion for qROPF valued functions, Hukuhara differentiability (H-differentiability) and \(α, β\) level-wise H-differentiability is defined. Using this KKT optimality condition for qROPF optimization problem with triangular qROPF objective function are formulated.